Digital Entrepreneurship of MSME Nagari Kamang Hilia - Deviana Ridhani (Institute of Computer Science (IOCS), 2022)
Nagari Kamang Hilia has a lot of potential for Micro, Small and Medium Enterprises (MSMEs) with multiple categories, namely food processing, trade, industry and services. The purpose of this research is to identify the potential for developing MSME products, especially Kamang Chips. This research method uses a descriptive qualitative methods through the process of observation, interviews and documentation presented in the form of data, then analysis using SWOT matrix analysis to determine strengths, weaknesses, opportunities and threats. The informants used as data sources are Walinagari Kamang Hilia, MSMEsNagari Kamang Hilia actors. The results of the research and discussion show that digital marketing can provide information and interact directly with consumers, expand market share, increase awareness and increase sales for MSME actors. The digital marketing of MSMEs Nagari Kamang Hilia is in the form of social media, Nagari website, and Nagari Podcasts.